MODULATION IN LEVELS OF INORGANIC IONS, DRY MATTER, AND NITROGEN FRACTIONS IN MULBERRY UNDER DIFFERENT MOISTURE REGIMES - RANJITHA KUMARI, B.D.; VEERANJANEYULU, A. (Annali di Botanica, 2019)
Influence of moisture stress on the levels of soil moisture (%) water potential, inorganic ions, dry matter and nitrogen fractions was studied in mulberry. Leaf water potential decreased with decrease in soil moisture level. Inorganic ions, calcium, potassium and sodium increased in roots and leaves with increasing intensity of stress. The reduction in dry matter of roots and leaves was higher in severe and very severe stress than in mild and moderate stress. The root and leaf total and protein nitrogen content decreased over control in all stress treatments. In contrast soluble nitrogen content increased with increase in stress treatments.